Analisis Pola Karakteristik Suara Pada Kasus Forensik - Dedy Prasetyo (Universitas Airlangga, 2018)
ABSTRACTAnalysis of voice characteristic pattern has an important role in the forensic science. It can apply to solve criminal cases in order to straighten justice and law in the Criminal Justice System. This study tries to analyze the pattern of voice print by comparing the evidence of recorded sound from the mobile phone with the sound of testee to determine their equality or difference. In answering the problem stated in the research hypothesis, then used comprehensive analysis based on voice acoustical characteristics, e. g. : spectrogram analysis, pitch statistical analysis, formant and formant bandwidth statistical analysis. Based on statistical test criteria with level of significance α = 0,05 reveals that the sound of evidence and the sound of testee are equal. Those sounds come from one person, in such a way that we can determine a suspect. Key words : Voice Analysis, Forensic Science, Criminal Justice System.